Severe traumatic brain injuries from motor vehicle‐related events in New Caledonia: epidemiology, outcome and public health consequences - Gilles Guerrier; Eloïse Morisse; Yann Barguil; Shirley Gervolino; Elisabeth Lhote (Elsevier, 2015)
Abstract Objective: Traumatic brain injuries (TBI), which are mostly due to road traffic crash (RTC), are a major public health concern. This article describes the incidence, severity and outcome of TBI caused by RTC in New Caledonia over a five‐year period. Methods: Data of all individuals admitted in intensive care unit with severe TBI (Glasgow Coma Scale score ≤8 at admission) caused by RTC in New Caledonia from 2008 to 2012 were analysed. Causes and severity of trauma, demographic data, and short‐term as well as last available long‐term outcome of patients were analysed. Five types of road users were compared (car drivers, car passengers, motorcyclists, bicyclists and pedestrians). Outcome was defined according to the Glasgow Outcome Scale classification. Results: A total of 109 patients were included in the study. The median age of patients was 24 [IQR18-33] years with a sex ratio of 2.8 (80 men/29 women). The rate of 44 among Melanesian males was two times higher that among 16 European males (22/100,000 people vs 11/100,000 people). The total survival at the Intensive Care Unit discharge (short‐term outcome) was 84%, being the highest among passengers (88%) and the lowest among motorcyclists (69%). Of the patients tested for psychoactive substances, half tested positive. Lost to follow‐up rate was 67%. Conclusion: Poor outcome occurs in patients with RTC‐related TBI, with young Melanesian men being the most affected. Public health action should focus on this group using culturally appropriate messages.